Research on relationship between cutting conditions and chip formation during end milling of aluminium alloy 6061 - Mohd Rasidi, Ibrahim; Najah, Mahadi; Afiff, Latif; Zulafiff, Rahim; Zazuli, Mohid; Mohammad Sukri, Mustapa; S. A., Che Ghani (Trans Tech Publications Ltd, 2017)
This paper studied chip morphology in end milling of aluminium alloy 6061 by various cutting parameter such as feed rate, cutting speed and depth of cut. Slot milling operation were conducted. The analysis consists of chip morphology, chip weight, chip thickness and chip length. Scanning Electron Microscope (SEM) were used to obtain and examine the chips. Result shows that, end milling with higher cutting speed, feed rate and depth of cut generated short, small and light weigh of chips.